TEORI PENGAMBILAN KEPUTUSAN DALAM ORGANISASI: KAJIAN KONSEPTUAL BERBASIS STUDI KEPUSTAKAAN - Nursahwal; Suban, Alwan; Rahman, Danial (Department of Islamic Education Management, 2025)
This article aims to discuss the theory of decision making in organizations. The type of research used is literature study by collecting data from primary sources such as books and journal articles. The data collection technique in this library study research is by browsing and reading various literature or written sources related to the research. The analysis technique used in this research is descriptive analysis, which goes through stages including identifying the topic and focus of the research, collecting literature and related sources, grouping information from the literature, presenting data systematically, understanding the context, and drawing conclusions. According to Stephen P. Robbins and Mary Coulter, the decision-making process is the most crucial thing for an organization in achieving short-term and long-term goals. Leaders need to formulate vision, mission and goals by considering internal and external factors. This decision-making process includes problem identification, information gathering, alternative evaluation, and decision implementation, and involves all team members. Good decisions can improve organizational performance, while bad decisions can have fatal consequences. Therefore, leaders must involve all parties in the decision-making process to ensure organizational success.